Manajemen Konflik Organisasi untuk Menjaga Komitmen dalam Unit Kegiatan Selam 387 Universitas Diponegoro - Meisa Aulia Rahma; Sri Budi Lestari (Interaksi Online, 2020)
Communication is a foundation in an organization to assist members in achieving goals both individual goals and organizational goals. But not infrequently there are obstacles in communication that result in a problem in the organization that results in conflict. Conflict is a natural thing in an organization, but if the conflict is not managed properly it will cause problems such as loss of member’s commitment. For conflict to have a positive impact on the organization, it must be managed using a specific strategy and known the causes. The purpose of this research is to find out the experience of individual organizations in organizational conflict management to maintain commitment in the Unit Kegiatan Selam 387 Diponegoro University. The theory used is the Conflict Management Style by Thomas and Killman to describe how conflict management is carried out by each member in the organization. This study uses a phenomenological approach to see individual experiences in organizational conflict management. The informants used in this study were 6 (six) people with characteristics who were members of Unit Kegiatan Selam 387 Diponegoro University, who had joined at least 1 year and could be interviewed. The results showed that the conflict in the organization originated from conflicts in individuals caused by a sense of saturation with organizational activities, interpersonal conflict caused by misunderstanding in communication, gaps between the forces and interventions from seniors and organizational conflict caused by unclear work status and overlapping responsibilities at work. Conflict resolution is done by informants, namely using compromising, collaborating, avoiding and the use of the third party involvement